Cartografia geomorfológica como subsídio para a análise das interferências do uso da terra no desencadeamento dos processos erosivos: Um estudo em área canavieira - Silveira, Alan [UNESP]; Da Cunha, Cenira Maria Lupinacci [UNESP] (My University, 2011)
This study aimed at analyzing the geomorphologic dynamics and its relationship to human interference and ownership of relief, towards a systemic approach, through the interpretation, in an integrated manner, of cartographic documents made from techniques of geomorphologic cartography and of land use. By stereoscopic pairs of aerial photographs, it was prepared the Geomorphological Map and the Land Use Map, respectively based on Tricart's (1965) and Ceron and Diniz's (1966) technical procedures. The unit of the research analysis refers to the basin of Tijuco Preto Streamlet (SP) which is located at the Geomorphological Province of São Paulo state Peripheral Depression between latitudes 22°42'17 and 22°51'36 S, and longitudes 47°30'30 and 47°37'03. In general, it was possible to notice that this basin has been experiencing linear erosion processes, where it was mapped many erosion furrows, grooving and creeping, besides several slope breaks. These processes are associated with a conjunction of circumstances, and the anthropic one is mostly represented by sugarcane monoculture and by urbanization, which are crucial agents in activating erosion processes and in direct interfering on the dynamics of river and rain flow at the basin of Tijuco Preto Streamlet.
The geomorphologic cartography as a subsidy to analyse the land use interferences in activating erosion processses: A study in a sugarcane area
Keywords: Erosion process and sugarcane monoculture; Geomorphologic dynamics; Land use; aerial photograph; cartography; erosion; geomorphological mapping; geomorphological response; land use; monoculture; slope failure; sugar cane; urbanization; Brazil; Sao Paulo [Brazil]